Effects of Co and Cr particles additions on phase transformation temperature of a Pb-Sn based alloy - Teker, T.; Kaplan, M. (Natl Inst Optoelectronics, 2011)
The effects of Co and Cr particle additions on the phase transformation temperature of a Pb-Sn alloy were investigated. The microstructure, mechanical and phase characteristics of the samples were examined by optical microscopy, tensile test and DTA analysis techniques. The additions of Co and Cr particles were found to decrease the toughness and ductility of the Pb-Sn alloy. The melting temperature of the Pb-Sn alloy is increased by Co and Cr particles but, the phase transformation temperature is decreased. The results obtained indicate that the phase transformation temperature of Pb-Sn based alloy can be controlled by Co and Cr particles.
Keywords: Casting; Mechanical; Thermal analysis